Low dose magnesium sulphate regimen and maternal outcome of patients with eclampsia - Banotra, Palvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Preeclampsia, a serious pregnancy complication which is commonly characterized by high blood pressure, presence of protein in the urine and sometimes swelling in women's feet, legs and hands. With this condition, patient’s high blood pressure often results in seizures. Generally, the outcome remains good, however, eclampsia can be life threatening and disastrous. Methods: This cross-sectional study considered 114 patients who meet inclusion criteria and agreed to will-fully participate in the study were evaluated for different parameters. Patients who developed eclampsia during intra-natal and postnatal period were included in the study. The aim of the study was to evaluate the maternal outcome among all patients of eclampsia treated with low magnesium sulphate dosage therapy. Results: The present study revealed, very low fit recurrence rate, low mortality rate, zero treatment failure rate, no toxicity and (99.12%) success rate. Conclusions: Apart from zero percent treatment failure rate, Low maternal mortality and fit recurrence rate encouraged us to continue the treatment with low dose MGSO4 regimen. Thus, low dose magnesium sulphate has been found very effective in treating the eclampsia and at the same time maintains the high safety margin.